Oxidation Process of H 2 O /UV for COD Reduction of Wastewater from Soybean Tofu Production - Pontas, Komala; Muslim, Abrar (UI Scholars Hub, 2015)
Chemical Oxygen Demand (COD) reduction of wastewater from soybean tofu production was studied by conducting advanced oxidation process (AOP) using hydrogen peroxide with UV radiation catalysts in a closed cylindrical glass reactor. The hydroxyl radical (*OH) concentration from H2O2 decomposition was modeled, and exponential trends were found for the *OH concentration over radiation time and operation temperature. As a result, it was found that the maximal *OH concentration was 0.209 mol L-1 at 240 minutes and 50 °C. The *OH concentration exponentially increased following rise in operation temperature. The H2O2/UV AOP application reduced COD concentration to approximately 42.41% from 10,545 to 6,073.2 mol L-1 at 240 minutes and 50 °C. In addition, the pseudo second order kinetics is a reliable model to present the COD reduction kinetics with the correlation coefficient R2 in the range of 95.9 to 99.4%. The kinetics constant increased with rise in operation temperature, and it was approximately 2.30E-07, 2.590E-07, and 3.03E-07 L mg-1min-1 for 30, 40, and 50 °C, respectively. The activation energy of COD reduction obtained was approximately 0.0138 J mol-1.